Leptospira seroprevalence and associated risk factors among cattle in Bor County, South Sudan - Kitale Estella John Kasiano; Lordrick Alinaitwe; Walter Okello; Tubihemukama Methodius; Christopher Joshua Aturinda; Ashiraf Lubega; Esther Sabbath Frazer Togo; Peter Micheal Marin; David Kal Onafruo; Ambrose Samuel Jubara; Savino Biryomumaisho; Clovice Kankya (PLoS ONE, 2025)
Leptospirosis is a bacterial zoonotic disease that is distributed globally. In livestock, leptospirosis often presents as a subclinical disease that results in significant reproductive and production losses, which could in turn have detrimental economic consequences, particularly in countries like South Sudan that rely on livestock farming for livelihood. Leptospirosis often presents as a subclinical disease in which case the animal may be a maintenance host for a specific serovar. Recent increases in unexplained abortions have prompted us to investigate Leptospira exposure and associated risk factors among cattle in Bor County South Sudan. A cross-sectional study was conducted between 22nd January to 15th February 2023. Blood samples were collected from 357 cattle in four of the six cattle camps in the County at that time. Seropositivity was determined by detecting anti-Leptospira antibodies in the serum samples by microscopic agglutination test (MAT) based on a panel of 12 serovars representing 12 serogroups. Data on risk factors were obtained using pre-tested questionnaires administered to the owner or herdsman of each sampled herd. Of the 357 cattle sampled, 66.95% (95% CI = 61.91–71.62) were seropositive (cut-off titer ≥100). Seventy-six of the seropositive cattle (21.65%) had MAT titer ≥800, indicating a probable recent infection at the time of sampling. The most prevalent serogroups were L. borgpetersenii Tarassovi (59.83%) and L. borgpetersenii Ballum (17.38%). In the robust Poisson regression model, only the age of cattle was a significant risk factor to Leptospira seroprevalence. The prevalence in adult cattle was 1.43 times higher than in young ones (95% CI 1.09–1.92; P-value = 0.012). The extremely high seroprevalence indicates that leptospirosis may be endemic in cattle in South Sudan, and potentially one of the etiologies for the recently increasing abortion reports. This may require confirmation of the infection status among the aborting cattle.